2002
DOI: 10.1002/cncr.10244
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise and immune system function in cancer survivors

Abstract: BACKGROUNDThere are a limited number of interventions for cancer survivors following completion of primary therapy that might reduce the risk of cancer recurrence and/or secondary malignancies and increase survival times. It has been proposed that physical exercise may be beneficial by enhancing the anticancer immune system response. The purpose of the current article is to: 1) briefly describe the immune system response to tumors, 2) discuss the impact of anticancer therapy on immune system function in cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0
11

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(95 citation statements)
references
References 55 publications
3
81
0
11
Order By: Relevance
“…Como factores explicativos de la asociación encontrada se puede considerar también el aporte del ejercicio moderado en la función inmunitaria de hombres y mujeres, aspecto que contribuye a explicar en cierta medida la menor frecuencia de incapacidad por causas médicas presentada en el grupo de personas activas (14).…”
Section: Discussionunclassified
“…Como factores explicativos de la asociación encontrada se puede considerar también el aporte del ejercicio moderado en la función inmunitaria de hombres y mujeres, aspecto que contribuye a explicar en cierta medida la menor frecuencia de incapacidad por causas médicas presentada en el grupo de personas activas (14).…”
Section: Discussionunclassified
“…[64][65][66][67] One possible underlying mechanism responsible for the age-associated increase in PC incidence is oxidative damage from ROS, such as superoxide, hydroxyl radical and hydrogen peroxide; 72,73 therefore, exercise could have a negative effect on PC by reducing these free radicals. Exercise has also been shown to improve innate immune function and surveillance, [68][69][70] and previous studies have demonstrated the importance of innate immune function on PC pathogenesis. [74][75][76][77][78] Exercise therapy and prostate cancer J Antonelli et al…”
Section: Proposed Molecular Mechanismsmentioning
confidence: 97%
“…[64][65][66][67] Exercise may also improve innate immune function and surveillance. [68][69][70] In addition, the reductions in systemic inflammation and pro-inflammatory factors seen with exercise have been postulated to decreased cancer risk. 71 Investigators in our group are beginning to explore alterations in angiogenesis as a potential molecular mechanism to explain the effect of exercise on PC pathogenesis.…”
Section: Proposed Molecular Mechanismsmentioning
confidence: 99%
“…En cuanto al componente celular, los mecanismos implicados comprenden: las células (NK) activadas por linfoquinas (LAK); los macrófagos que constituyen una defensa de primera línea contra el CA y son capaces de disminuir la incidencia, progresión y metástasis de algunos tumores; los neutrófilos y células asesinas naturales, y nivel de los factores solubles la proteína C-reactiva, la interleucina 1 (IL-1), el factor de necrosis tumoral (TNF-α) y el interferón (IFN) (Fairey, Courneya, Field y Mackey, 2002b).…”
Section: Sección Centralunclassified
“…Por el contrario, estudios realizados en animales con ejercicio de alta intensidad demuestran un mejor efecto de este tipo de ejercicio que el de baja y moderada intensidad sobre el sistema inmune innato (Fairey et al, 2002b).…”
Section: Sección Centralunclassified